Training needs assessment for transformation of smallholder livestock farming in Botswana - Tselaesele, N.M.; Bagwasi, N.; Lepetu, J.; Bahta, Sirak T.; Oladele, I.O. (Academy of Science of South Africa, 2018)
The need to improve the competitiveness of smallholder livestock owners in Botswana was studied through Training Need Assessment (TNA) with the aim of strengthening the capacity of agricultural education and extension in the livestock sector. TNA was conducted in selected areas of Botswana namely, Mogobane, Boatle and Taung villages in the South-East District as well as Serowe, Bobonong, Nata and Letlhakane in the Central District of Botswana. A simple random sampling method was used to select 395 smallholder livestock farmers. Quantitative and qualitative data were collected using a questionnaire and focus group discussions respectively. Quantitative data was analysed using means (and standard deviations). The results from focus groups were based on the coding of themes that emerged from the discussions. The results show that smallholder livestock farmers were lacking knowledge and skill in some of the following topics: Farm records and accounts; artificial insemination; feeds and feeding which include nutritional diseases and range management. It is recommended that livestock marketing, which is an important component in livestock production, be integrated into all livestock extension training programmes. Furthermore, the inclusion of diagnosis of livestock diseases, vaccination and borehole maintenance is also recommended.